As ações político-pedagógicas do Serviço de Assistência Rural-SAR - Correia, Cícero Gomes (2005)
This program resumes the history of the political-pedagogic actions on the Serviço de Assistência Rural SAR, of Natal archdiocese, and analyses the contributions of this actions on the process of rural workers organization in the social movements on the countryside. The educative actions of the RAS are happening in a permanent tension between the pedagogic project of a church in change and, a pedagogy of the groups, communities and social movements, that is centered in the cultural action, in the culture lived from its condition of citizens. This research reveals that this entity fulfilled a strategic attribution for the Natal s church on the formation of the community leaderships, at a first moment and leaderships for social movements. Before the military dictatorship, the work methodology of this entity had as priority, begin from the reality leaved by the rural workers in the expectation that these became to qualify themselves for a more citizen participation in the call development. During the military regime, the entity goes measuring theirs activities in the new context, until the moment that redefines the work line. Goes then defining regions and thematic of operation supporting the fights for land, salary campaigns, women agricultural workers organizations. The pedagogy of work has as one of its supporters the Paulo Freire s pedagogy, privileging the dialog as a source of production of knowledge from the reality leaved in a permanent transformation. The actions of this entity, with the groups and social movements, produces the necessary knowledge for the organization of the rural workers while individual and social subjects of a changing world. The process of action-reflection of the activities intended, by a creative form, a permanent production of strategies of fight of the workers. Research ever, not to make accommodate itself to the new knowledge acquired in the action-reflection it is part of the pedagogical idea of this Institution. One searched in this process of formation of the man and the woman to question the reality, to create actionreflection-action spaces on the fights for a possible transition of an ingenuous conscience for a critical conscience, in view of the transformation of the structures that oppresses them